Opportunities for Keeping Talent Highlighting Career Needs - Gergely, Éva; Pierog, Anita (International Journal of Engineering and Management Sciences, 2018)
Organizations should focus not only on finding a workforce, but also on finding a talented employee and to be able to keep them. That is why we considered it important to pay attention to talents and careers. In this paper, we attempt to identify those factors which are important for career prospects among future employees and those already in the workforce. Moreover, we want to identify the factors which those who are already employed consider to be factors influencing their career prospects. We conducted a survey of students using questionnaires. 116 questionnaires were completed, of which 73 were filled in by BSc / BA students and 43 by Msc / MA students. We sought to discover to what degree the respondents considered the career factors we presented them with as influencing their ability to acquire an ideal job, as well as to what degree the same career factors would be able to assist them in their future career advancement. Presently, in their roles as students seeking gainful employment, important factors include perseverance, diligence, knowledge, and aptitude, all of which the respondents feel will become even more important in making their later advancement possible. At present, they do not consider the support of companions / partners and morality important; but they consider the support they receive from their colleagues to be a factor which grows in importance over time. In the questionnaire survey of employees, we were looking for two answers. On the one hand, which factors are important in shaping their careers, and on the other hand, at the workplace, which factors were related to employee retention and satisfaction. For their careers, they consider it important to have diligence, morality, and the support of colleagues. These results are similar to the views expressed by the students. However, those who already work consider ‘kissing up to the boss’ to be more important for their advancement possibilities than the students did. The responses concerning factors contributing to successful employee retention brought interesting results. Factors that are most commonly fulfilled, such as a good co-worker relationship and the working relationship with a leader, are barely above the average score of 4, which is actually a result that is above average. Medium results include the realization of independence, challenging work, fair pay and career prospects factors, all of whcih would be vital for talented people to experience flow in their careers. In the long term, leaders and HR professionals need to pay attention to take calculated, equisite steps to keep talented workers.